Behavioral variability and autism spectrum disorder. Issue 1 (8th October 2014) - Rodriguez, Nicole M.; Thompson, Rachel H.
Abstract Restricted and repetitive behavior is a diagnostic characteristic of autism spectrum disorder (ASD). To the extent that the behavior of individuals with ASD can be conceptualized as problems of invariance, our understanding of environmental variables that influence restricted and repetitive behavior may be informed by the basic and applied literature on response variability. The purposes of this paper are (a) to describe how restricted and repetitive behavior can be conceptualized as problems of invariance, (b) to consider the implications of a lack of varied responding for individuals with ASD, (c) to review relevant basic and applied research on response variability, (d) to present methods to address invariant responding for individuals with ASD, and (e) to suggest areas for future research.